ð˜—ð˜¦ð˜³ð˜ªð˜ð˜ªð˜µð˜¶ð˜´ ð˜¤ð˜°ð˜¤ð˜¤ð˜ªð˜¯ð˜¦ð˜ð˜¢ð˜¦ (SCHRANK, 1802) (HYMENOPTERA, BRACONIDAE, EUPHORINAE) PARASITO DE ð˜Šð˜°ð˜ð˜¦ð˜°ð˜®ð˜¦ð˜¨ð˜ªð˜ð˜ð˜¢ ð˜®ð˜¢ð˜¤ð˜¶ð˜ð˜¢ð˜µð˜¢ (DEGEER) (COLEOPTERA, COCCINELLIDAE) - Berti Filho, Evoneo; Costa, Valmir Antonio (REVISTA DE AGRICULTURA, 2020)
ð˜—ð˜¦ð˜³ð˜ªð˜ð˜ªð˜µð˜¶ð˜´ ð˜¤ð˜°ð˜¤ð˜¤ð˜ªð˜¯ð˜¦ð˜ð˜¢ð˜¦ (SCHRANK, 1802) (HYMENOPTERA, BRACONIDAE, EUPHORINAE) PARASITO DE ð˜Šð˜°ð˜ð˜¦ð˜°ð˜®ð˜¦ð˜¨ð˜ªð˜ð˜ð˜¢ ð˜®ð˜¢ð˜¤ð˜¶ð˜ð˜¢ð˜µð˜¢ (DEGEER) (COLEOPTERA, COCCINELLIDAE)